Research on indoor positioning algorithm based on visible light communication - Daming ZHAO; Xin WANG (Dianxin kexue)
VLC is a green communication technology that realizes communication while using white LED solid-state light source for illumination.Through the research on visible light communication technology,combined with the positioning accuracy improvement algorithm,a low-cost,low-power,high-precision,illumination-enabled visible light positioning solution was proposed.System scheme and channel model,signal receiving and processing technology,high precision positioning algorithm,image assisted technology were analyzed.